Extração, propriedades funcionais e aplicação tecnológica da mucilagem da Talinum paniculatum (Jacq.) Gaertn - Castro, Luiza Sousa de (2024)
Brazil, the country with the highest biodiversity in the world, still exploits its vast potential in a limited way, especially in the area of natural food additives, fundamental for the production of healthier foods. The growing concern about health risks associated with excessive consumption of phosphates has stimulated the search for natural alternatives to replace these additives in meat products. In this context, this study aimed to extract and characterize the mucilage of the roots of the unconventional food plant (UFP) Talinum paniculatum (Jacq.) Gaertn and evaluate its viability as a substitute for sodium tripolyphosphate in skin emulsions. The mucilage extraction was carried out by crushing the roots, followed by hydration with water and centrifugation, with subsequent drying in an oven or lyophilization. The mucilage obtained was subjected to a comprehensive chemical characterization, including the amino acid profile and carbohydrate determination, as well as the evaluation of its biological properties, such as antimicrobial and antioxidant activity. Functional properties such as emulsifying capacity, emulsion stability, foaming ability and stability, solubility, water retention capacity and rheological behavior were also investigated. The thermal properties of the mucilage were analyzed by differential scanning calorimetry (DSC), thermogravimetry (TG) and infrared spectroscopy with Fourier transform (FTIR). The lyophilization process was more efficient, resulting in a higher mucilage yield (1.17% 0.25), with pH of 6.32 0.03. The chemical profile analysis revealed scores below 1.0 for all amino acids, with the highest level presented by tryptophan (0.40), in addition to a high total glucose content. However, antimicrobial and antioxidant activities did not show significant results (p>0.05) in the evaluated conditions. In terms of functionality, the mucilage demonstrated excellent emulsifying capacity and emulsion stability (93.75%), high formation capacity and foam stability at different pH levels and good water retention capacity (288.94 27.39 g water/g mucilage). The thermal stability of the mucilage was confirmed by DSC and TG analysis. When applied in skin emulsions, it did not significantly alter (p>0.05) the hardness and elasticity of the emulsions. However, there was a reduction in chewing and gum, as well as a lower shear force, resulting in a softer texture. The mucilage emulsions presented a lower L* value (indicating darker color) compared to formulations with sodium tripolyphosphate, without significant changes in the values of a* (red/green) and b* (yellow/blue). It is concluded that the mucilage of T. paniculatum presents promising functional properties for the substitution of sodium tripolyphosphate in meat emulsions, maintaining the desirable sensory characteristics of the final product. This substitution contributes to the production of potentially healthier foods, aligned with current demands for food products with natural and less processed additives. Thus, the exploitation of Brazilian biodiversity through the use of UFP as T. paniculatum can offer sustainable and innovative alternatives for the food industry.